"Mobility game": interactive technology for urban planning education. Issue 1 (March 2020) - Danilina, N V; Harder, R
Abstract: Modern trends in the development of urban planning education dictate the need to implement new innovative technologies for comprehension of urban processes. The idea «from Smart Cities to Smart Territories» determines the current interest for the introduction of software systems that allow students creating and studying a smart urban environment. The article is devoted to the introduction of interactive technologies to improve the quality of the educational process in the field of urban planning. The relevance of the topic is due to modern trends in the digitalization of the urban environment. The purpose of the study is to determine the role and importance of interactive technologies in the formation of professional competencies of students in the planning and design of a smart city and its transport system. There is the analysis of possibilities of the software complex "Mobility game". This interactive game allows creating a city and developing its transport infrastructure based on specific quantitative and qualitative parameters of development of the road network, the composition of the transport system and the mobility of the population. The software package takes into account modern trends in the development of smart urban transport, such as changes in the composition of the traffic flow, increasing the number of micro-cars and passenger transport, the rapid development of information technologies for travel support, and allows students visually exploring the interaction and mutual influence of various parameters in practical classes. The application spectrum of this software is broad. In addition to communicating essential relationships between urban development issues and the necessary transport infrastructure in education contexts, local planning situations can also be modelled using defined scenarios. The implementation of interactive technologies is a proven scientific and practice-oriented tool for this purpose.